Metode Question Students Have dalam Meningkatkan Hasil Belajar Aqidah Akhlak di Kelas IX MTs Hidayatul Mubtadiin Desa Sidoharjo Kecamatan Jati Agung Lampung Selatan - Anisa Istiqomah; Muhammad Yasin; Suci Hartati (Journal on Education, 2024)
The main objectives of this research are: 1) What is the Question Method Students Have in Improving Moral Creed Learning Outcomes in Class IX A of Madrasah Tsanawiyah Hidayatul Mubtadiin. 2) What are the factors and supports in using the Question Students Have Method in improving learning outcomes of moral beliefs in class IX A Madrasah Tsanawiyah Hidayatul Mubtadiin. This research method uses a qualitative approach. The method used in this research is observation, interviews, documentation. The results of the research show that the Question Students Have method can improve Akidah Akhlak learning outcomes in class IX A of Madrasah Tsanawiyah Hidayatul Mubtadiin, namely: Increasing students' absorption of learning materials, training their ability to work together, hearing other people's opinions and improving their memory of the material they have learned. studied, Improving student learning outcomes with the abilities they already have, especially in learning Moral Creeds. Supporting factors are; Internally, the factors that students must have are intelligence in students, interest in learning and attention, motivation to learn, as well as the physical condition and health of the students themselves. Inhibiting factors are: external factors, namely the infrastructure that must be owned by the Madrasah, the Madrasah environment itself, the family environment and the students' own interactions.